Idea selection using innovators and early adopters. Issue 4 (31st December 2018) - Sääksjärvi, Maria; Hellén, Katarina
Abstract : Purpose: Development of new products is important for firm success; however, firms often struggle to identify the best ideas from multiple options. The purpose of this paper is to study how innovators and early adopters can be used for identifying the best ideas, i.e. the ideas that appeal to mass-market customers. Design/methodology/approach: Two empirical studies were conducted. Study 1 concerned the development of a symbolic innovation, whereas Study 2 focused on a functional innovation. Each study consisted of two parts: idea generation and idea evaluation. In Study 1 there were 124 idea generators and 248 idea evaluators. In Study 2 there were 104 idea generators and 108 evaluators. Findings: Both studies demonstrate that innovators and early adopters are able to predict the ideas that appeal to mass-market customers. Yet, it was also shown that this prediction depends on the nature of the idea. In the case of ideas for products that are predominantly symbolic in nature (Study 1), innovators and early adopters predict the buying intentions of mass-market consumers via the perceived novelty of the idea. In turn, for ideas that are predominantly functional in nature, innovators and early adopters predict the buying intentions of mass-market consumers directly via buying intentions. Originality/value: These findings show that innovators and early adopters can be used for selecting the best ideas from a plethora of available options. This is the first time that innovators and early adopters have been empirically demonstrated to hold such a role.